Molecular communication - Nakano, Tadashi 1912-; Eckford, Andrew W.; Haraguchi, Tokuko (Cambridge University Press, 2024)
Fully revised and updated, this second edition is a comprehensive introduction to molecular communication including the theory, applications, and latest developments. Written with accessibility in mind, it requires little background knowledge, and carefully introduces the relevant aspects of biology and information theory, as well as practical systems. Capturing the significant changes and developments in the past decade, this edition includes seven new chapters covering: the architecture of molecular communication; modelling of biological molecular communication; mobile molecular communication; macroscale systems; design of components and bio-nanomachine formations. The authors present the biological foundations followed by analyses of biological systems in terms of communication theory, and go on to discuss the practical aspects of designing molecular communication systems such as drug delivery, lab-on-a-chip, and tissue engineering. Including case studies and experimental techniques, this remains a definitive guide to molecular communication for graduate students and researchers in electrical engineering, computer science, and molecular biology